2018
DOI: 10.1016/j.envint.2018.07.038
|View full text |Cite
|
Sign up to set email alerts
|

A review of factors surrounding the air pollution exposure to in-pram babies and mitigation strategies

Abstract: Air pollution exposure to in-pram babies poses a serious threat to their early childhood development, necessitating a need for effective mitigation measures. We reviewed the scientific and grey literature on in-pram babies and their personal exposure to traffic generated air pollutants such as particulate matter ≤10 μm (PM), ≤2.5 μm (PM), ≤0.10 μm (ultrafine particles) in size, black carbon and nitrogen oxides and potential mitigation pathways. In-pram babies can be exposed up to ~60% higher average concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 115 publications
(140 reference statements)
1
8
0
1
Order By: Relevance
“…However, our study has provided evidence to support previous literature observations (Kenagy et al 2016) that the standard practice of locating diffusion tubes at heights either at or above adult breathing height in the UK may lead to an underestimation of the concentration of NO 2 experienced by children, either walking or in prams and buggies. These concerns have been highlighted in the literature for nitrogen dioxide, particulate matter and other pollutants (Sharma and Kumar 2018). In the present study, at site 1, we found that NO 2 concentrations over an 8-month period were 5.9% lower at the NCC standard diffusion tube height (2.7 m) compared with at children's breathing height (0.7 m).…”
Section: Public Health Implicationssupporting
confidence: 51%
See 1 more Smart Citation
“…However, our study has provided evidence to support previous literature observations (Kenagy et al 2016) that the standard practice of locating diffusion tubes at heights either at or above adult breathing height in the UK may lead to an underestimation of the concentration of NO 2 experienced by children, either walking or in prams and buggies. These concerns have been highlighted in the literature for nitrogen dioxide, particulate matter and other pollutants (Sharma and Kumar 2018). In the present study, at site 1, we found that NO 2 concentrations over an 8-month period were 5.9% lower at the NCC standard diffusion tube height (2.7 m) compared with at children's breathing height (0.7 m).…”
Section: Public Health Implicationssupporting
confidence: 51%
“…The official guidance acknowledges that tubes placed at heights above the breathing zone may 'underestimate the actual concentrations to which the public are exposed' (AEA Energy and Environment 2008). The average breathing height of children ranges from 0.7 to 1.5 m (Rivas et al 2016), whereas children in prams and strollers have breathing heights of approximately 0.55 m and 0.85 m respectively (Sharma and Kumar 2018). Therefore, children will experience NO 2 concentrations at heights that are as much as 2 m below what is being monitored and reported by NCC.…”
Section: Introductionmentioning
confidence: 99%
“…This clearly supported the sudden change in the PM2.5 levels. After further inspection of the data during this event, the participant found that it took almost 12 hours for the concentration level to go back to normal since the burning incident, clearly highlighting that PM2.5 concentrations can disproportionally increase during such incidents to expose families, including most vulnerable such as young children (Sharma and Kumar 2018) and elderly people (Segalin et al, 2017), to harmful level of pollution. The citizen scientist highlighted the need for sufficient ventilation in kitchens, especially the importance of opening the windows, during food burning events, where PM2.5 concentrations can take hours to return to normal levels without sufficient ventilation.…”
Section: Burned Food In My Kitchen Took Hours To Reach Pm Levels To Nmentioning
confidence: 99%
“…The majority of people living in nearroad environments are low-income residents or minorities (Carrier et al, 2014a;Tian et al, 2013). In addition, exposure to traffic-related air pollutants of vulnerable schoolchildren escalates concerns over air quality in the near-road region (Carrier et al, 2014b;Kim et al, 2004;Kumar et al, 2017;Sharma and Kumar, 2018). Numerous studies have demonstrated the association of adverse health impacts with people living in near-road conditions proximate to highways.…”
Section: Introductionmentioning
confidence: 99%